A techinique of saturating vermiculite with cationic micronutrients - Kinjo, Toshiaki; Silveira, Ronaldo Ivan; Marconi, Arary; Abrahão, Ibrahim O. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
The purpose of this work was to study a method of saturating vermiculite with cationic micronutrients, such as zinc, copper, manganese, and iron. The technique used was to react H - saturated vermiculite with hydroxides of micronutrients. During the reaction, there should occur neutralization of H+ ion of the vermiculite and adsorption of the micronutrients in the mineral. The results of micronutrients extracted by 0.1 N HC1 and 0.5 N NH4OAc pH 4.8 showed that the saturation of zinc and copper worked well. For manganese, its precipitation as hydroxide should be done in the pH greater than 8.5 in order to get total precipitation. The method also worked for the saturation of iron, but its solubility In the solution of 0.5 N NH4OAc pH 4.8 was very low.